Relative Impacts of Simultaneous Stressors on a Pelagic Marine Ecosystem - Woodworth-Jefcoats, Phoebe A.; Blanchard, Julia L.; Drazen, Jeffrey C. (Frontiers in Marine Science, 2019)
Climate change and fishing are two of the greatest anthropogenic stressors on marine ecosystems. We investigate the effects of these stressors on Hawaii’s deep-set longline fishery for bigeye tuna (Thunnus obesus) and the ecosystem which supports it using a size-based food web model that incorporates individual species and captures the metabolic effects of rising ocean temperatures. We find that when fishing and climate change are examined individually, fishing is the greater stressor. This suggests that proactive fisheries management could be a particularly effective tool for mitigating anthropogenic stressors either by balancing or outweighing climate effects. However, modeling these stressors jointly shows that even large management changes cannot completely offset climate effects. Furthermore, when climate change and fishing are considered together, their effects are to some degree synergistic. Our results suggest that a decline in Hawaii’s longline fishery yield may be inevitable. The effect of climate change on the ecosystem depends primarily upon the intensity of fishing mortality. Management measures which take this into account can both minimize fishery decline and support at least some level of ecosystem resilience.